Scientometric Analysis of Activated Carbon or Probiotics in Mouthwashes or Toothpastes: Dynamicity, Spatiotemporal Evolution and Trends - Mauricio, Franco (2024)
The use of activated charcoal and probiotics is a controversial topic nowadays due to their potential oral health benefits. Thus, the aim of this research was to perform a scientometric analysis of activated charcoal or probiotics in mouthwashes or dentifrices by means of dynamicity, spatiotemporal evolution, and trends. A study was carried out to look back at scientific publications between 2005 and 2022 using the Web of Science. To analyze the data, various bibliometric indicators were used. The process of retrieving information was completed on July 28, 2023. It was found that only 1 article was published in 1990. Furthermore, the highest co-citation occurred in cluster 9 (Dentistry, Dermatology, Surgery), indicating a higher relevance and frequency with cluster 8 (Molecular Biology, Genetics). In the cluster view, 15 large clusters were identified, with cluster 0 (Activated Carbon) being the largest and occupying the greatest centrality. On the other hand, the cross-country collaboration map showed active collaborations between Australia and New Zealand, Brazil, and Canada. We found a significant growth of scientific publications on probiotics and activated charcoal in the field of dentistry and related disciplines between 1990 and 2023.